Rentabilité du trinôme Caféier/Cacaoyer/Palmier à huile dans les agrosystèmes de Santchou (Ouest Cameroun) - Hippolite AZAOU (Revue Hybrides)
With the coffee crisis of the 90s and the liberalization policy that followed, the agricultural sector in the West region of Cameroon has undergone changes. Under the leadership of innovative producers, a rare coffee/cocoa/palm oil system has emerged and brings hope to the smallholders. This article aims at assessing the profitability of this system in the agro-ecosystems of Santchou. Surveys were carried out with 400 producers distributed all over the three production area. The results show that the smallholders’ perceptions of this reconstitution of the rural landscapes of Santchou are positive. Since the coffee crisis, the diversification of cash crops has led to an increase in income of 97.8% of producers. Though these producers are not yet safe from financial difficulties, the diversification of income crops leads to an improvement of their living standards and a development of the locality. Despite the limitation of constraints in this diversification and the problem of the system’s sustainability, the new coffee/cocoa/palm oil trinomial is a source of hope for nearly ¾ of producers. Hence, the need for government supports to ensure the sustainability of this system.